Derivation of Schrodinger Equation from Maxwell Electric Equation - Sami Abdalla Elbadawi (Genius Journals, 2022)
Maxwell's equations can be used to derive Schrodinger equation. The polarization term is used to find the energy term. One can use plank quantum hypothesis beside Einstein mass energy relation to find a useful expression for Maxwell electric equation. Replacing the electric field intensity by the wave function one found Schrodinger quantum equation.
Keywords: Maxwell's equations; Schrodinger equation; plank hypothesis; Einstein mass energy relation